On history and salvation in Emmanuel Levinas and Ernst Bloch - Terreblanche, Salomon J. (HTS teologiese studies, 2008)
This article explores the tension between history and salvation as theme in contemporary social and humanist philosophy. Special reference is made to Emmanuel Levinas’ work in order to delineate the scope of the questions involved, and to critically elucidate the position on history, death and hope in new-Marxist philosopher Ernst Bloch. The article then illuminates Levinas’ phenomenological account of fecundity, parenthood, patience and institutional justice as hopeful moments that are contained in his philosophy on history